Development and evaluation of tractor operated ditcher cum bed-former for pineapple cultivation - AMBILY S. PRASAD GISS MERIN VARGHESE SAIDALAVI M; Dr. V. R Ramachandran (Guide) (Tavanur 2003 Kelappaji College of Agricultural Engineering and Technology)
the main components of the prototype unit of the tractor operated pineapple ditcher cum bed-former are a mould board, standard, levellers and main frame
Development and evaluation of tractor operated ditcher cum bed-former for pineapple cultivation